Effective Incubation as One of the key Support Measures in Fostering Growth of SMMEs in South Africa - Chonela, Thato (My University, 2011)
This report explores and highlights the effectiveness of incubation as one of the key factors that can foster growth in the South African SMMEs sector. The SMMEs in South Africa could potentially benefit from the effective and efficient incubation programs run by different stakeholders in the market. The study reviews the progress and the challenges of the three main stakeholders which are the government, the private sector and the NGOs in providing incubation services to the South African SMMEs sector. A total of 14 responses were gathered from the three major stakeholders to inform the findings of the study. The study discovered quite a number of different aspects that needs to be considered when establishing an incubation program and the different incubation models that could become a framework in designing effective incubation program. The study revealed that the SMMEs failure rate is still high in South Africa and therefore effective incubation has an important role to play in turning SMMEs into HGSMEs and reduce failure rate in the South African SMME‟s sector. It is through collaboration of efforts from all the major stakeholders that the process could speed up and bring about the desired results. Incubation is just one of the business development services needed by entrepreneurs but it carries more weight and could undeniably uplift the South African SMMEs sector.
MM thesis - P&DM
Keywords: Business incubation; Small, medium and micro businesses